2016
DOI: 10.1021/acs.jpca.6b10098
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electronic Wave Functions of Sodium-Doped Clusters: Dyson Orbitals, Anisotropy Parameters, and Ionization Cross-Sections

Abstract: We apply high-level ab initio methods to describe the electronic structure of small clusters of ammonia and dimethyl ether (DME) doped with sodium, which provide a model for solvated electrons. We investigate the effect of the solvent and cluster size on the electronic states. We consider both energies and properties, with a focus on the shape of the electronic wave function and the related experimental observables such as photoelectron angular distributions. The central quantity in modeling photoionization ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…41,42 For photoionization or photodetachment from open-shell doublet species producing a closed-shell state, one can employ the reference state corresponding to the ionized closed-shell state and use EOM-EA (EOM for electron attachment, where the EOM operators add an electron to the reference) to describe the initial doublet state. 43 In the case of photoionization of O( 3 P) and OH( 2 Π), however, both the initial and the final states are of open-shell character (see Fig. 1).…”
Section: B Theorymentioning
confidence: 99%
“…41,42 For photoionization or photodetachment from open-shell doublet species producing a closed-shell state, one can employ the reference state corresponding to the ionized closed-shell state and use EOM-EA (EOM for electron attachment, where the EOM operators add an electron to the reference) to describe the initial doublet state. 43 In the case of photoionization of O( 3 P) and OH( 2 Π), however, both the initial and the final states are of open-shell character (see Fig. 1).…”
Section: B Theorymentioning
confidence: 99%
“…[36][37][38][39][40][41] Here, the simplest approach is to model the outgoing electron as a free particle or a distorted wave corresponding to an effective Coulomb potential, [42][43][44] which has been in particular applied to PES studies of rather large molecules. [45][46][47][48][49] Finally, an entirely different set of methods relies on an implicit continuum representation with Stieltjes imaging [50][51][52][53] or a Green's operator formalism. 54 However, energies of several hundreds of eV, targeted in X-ray PES and RAES necessitate large basis sets leading to demanding computations.…”
Section: Introductionmentioning
confidence: 99%
“…Magic numbers play a central role in cluster science (see references on molecular clusters [1][2][3][4][5][6][7][8][9][10][11][12] ). Usually, these magic numbers are related to the high stability of clusters of certain sizes.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,13,14 This is because measurements of photoelectron angular distributions (PADs) of clusters are not so common and the modelling of cluster PADs is demanding. 5,10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Typically, a prerequisite for the observation of magic numbers in the photoelectron anisotropy is a high cluster symmetry that results in orbitals with high fractional scharacter. 10,13,14,24 In our recent studies, 10,24 we reported the first observation of magic numbers in the photoelectron anisotropy of solvated electrons in Na-doped clusters of dimethyl ether, ammonia, methanol and water.…”
Section: Introductionmentioning
confidence: 99%